THE LINGUISTIC FEATURES OF NATIONAL ORNAMENTS AND THEIR CONNECTION TO LANGUAGE AND DESIGN (Journal of Universal Science Research, 2025)
National ornaments are more than mere decorative patterns; they are rich in cultural significance and can be understood as a form of visual language. This article explores the linguistic features embedded in national ornaments, examining how their symbols, patterns, and forms convey meanings that parallel language and communication. By analyzing examples from various cultures, the article highlights the intricate connection between language, design, and cultural identity. It also discusses the evolving role of these ornaments in contemporary design and their continued relevance in understanding the relationship between culture, language, and visual aesthetics.